Improvement of short circuit testing preparations in a low voltage testing laboratory - Syrjälä, Juho (My University, 2017)
Product standards for low voltage switches describe type tests that need to be per-formed to ensure the safety of the switches. Short circuit tests are part of these tests and the staff of ABB Oy Protection and Connection testing laboratory wants to improve the preparations of the tests. As one objective, the short circuit testing process in the laboratory is documented in this thesis. Another objectives are to improve the technical preparations of the AC short circuit tests by creating a new more flexible calculation tool and by suggesting improvement ideas for load components needed in the test circuit building. Short circuit currents in the laboratory are generated with a synchronous medium volt-age generator and a high-current transformer with medium and low voltage sides. Test circuits of short circuit tests must follow power factor values defined by the product standards. To fulfill the power factor demand the test circuit’s reactance and resistance must be set with adjustable load reactors and load resistors. The load reactors and load resistors for AC short circuit tests are located on the medium voltage side. Values for the load components are obtained through short circuit calculation. Test current, test voltage, power factor from a product standard and values from old test current calibrations are used to calculate the load component values. Comparison to old calibrations is needed to see how much additional reactance and resistance other components in addition to the load components add to the test circuit. Preparations of the short circuit tests can be expedited by using average additional resistance and reactance values that are generated from old calibration records. In addition, knowing the reasons for the additional resistance and reactance and automated features of the new calculation tool can expedite the preparation phase. Also, benchmarking to the practices of another testing laboratory proved to be an effective way to find fresh ideas for load component development. Two implementation ideas for new component placing were created based on the component comparison.
Keywords: Short circuit testing; low voltage switch; load reactor; load resistor; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|